Normative Reposition of Regional Head Regulations in the Indonesian Legal System - Kolang, Al Rhega Caesar Grestiano (Universitas Islam Negeri Raden Intan Lampung, 2025)
Regional head regulations as regional government implementers based on the principle of regional autonomy are posited in two aspects: statutory regulations and policy rules. This sometimes leads to forming regional head regulations in the name of beleid (kebijakan) without any normative foundations. Furthermore, the implications of these two positions are theoretically important in the discourse of administrative law [studies]. Based on this matter, this paper aims to examine the position of regional head regulations in its dual position and then decide its normative [re]position in the Indonesian legal system. For this reason, the research questions in this paper are: What is the normativity of regional head regulations among their position as statutory regulations or policy rules in the Indonesian legal system? The research method used in this paper is doctrinal legal research with a conceptual approach and a statutory approach. Based on the research results, this paper argues that regional head regulations are statutory regulations and no longer have a duality of position, especially as material policy rules. Therefore, this paper concludes that every creation of regional head regulations must be based on the provisions of attribution and delegation as well as being the object of juridical control in the form of judicial review and executive review.